EFEKTIVITAS PROGRAM BILINGUAL DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA - Putri, Rasya Agustantia; Hamidiyah, Aisyah; Fajrudin, Lili (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the implementation of the bilingual program in improving students' English speaking skills at Tiara School. The research uses a descriptive qualitative method, with the subjects being the school principal, English teachers, and third-grade students at Tiara School. Data for this study were collected through observations, interviews, and documentation. The data analysis technique involved data collection, data reduction, data presentation, and drawing conclusions or verification. The data were then tested for validity using techniques such as credibility, transferability, dependability, and confirmability. The results of the study show that the implementation of the bilingual program, such as Cooking Class, English Festival, and subjects like English, Science, and Math, as well as daily practices at Tiara School, significantly improved the students' English speaking skills. This can be seen from the students' speaking scores over the year, from the second semester of grade II to the second semester of grade III. The average score of students in the second semester of grade II was 87.35, and in the second semester of grade III, it increased to 90. The improvement from 87.35 to 90 indicates a significant enhancement in students' English speaking skills.